2021
DOI: 10.1177/08997640211057452
|View full text |Cite
|
Sign up to set email alerts
|

Nonprofit Board Governance Policy Adoption: Toward an Integrated Board Interlock Network and Institutional Perspectives

Abstract: Previous research lags behind in illuminating theoretical mechanisms that shape governance decision-making on board practices. Using an integrated theoretical approach, I examine how board interlock network and institutional factors are associated with board governance policy adoption in nonprofit organizations. A linear regression model is employed to investigate policies adopted by a panel of public charities in three cities in Upstate New York during 2008 and 2014. Results show that not only the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…Existing studies (27.78%; 5 of 18) tend to focus on how NPOs could benefit from implementing “formal policies” to avoid fraud and prevent future misconduct (Archambeault & Webber, 2018; Bromley & Orchard, 2016) as well as to allow them to gain and maintain stakeholders' trust, support, and contribution (Dhanani & Connolly, 2012; Lee, 2016). In this sense, written standards and networks may help promote governance practices (Yoon, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Existing studies (27.78%; 5 of 18) tend to focus on how NPOs could benefit from implementing “formal policies” to avoid fraud and prevent future misconduct (Archambeault & Webber, 2018; Bromley & Orchard, 2016) as well as to allow them to gain and maintain stakeholders' trust, support, and contribution (Dhanani & Connolly, 2012; Lee, 2016). In this sense, written standards and networks may help promote governance practices (Yoon, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, scholars examining nonprofit board interlock attend to outcomes such as the acquisition of foundation grant funding through the signaling function of interlocking board members (Esparza & Jeon, 2013; Faulk et al, 2016, 2017; Paarlberg et al, 2020). In a recent study, Yoon (2021b) and Bloch and colleagues (2020) showed empirical evidence that nonprofits with interlocking board members report more extensive use of governance practices targeted to enhance governance operations. Related studies also emphasize how nonprofit networks contribute to organizational performance, growth, and survival through an external representation function of network ties (Galaskiewicz et al, 2006; Hager et al, 2004; Pfeffer & Salancik, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have explored the organizational connections that are established by means of top leaders holding multiple positions in several CSOs (see next section). When in focus, studies have explored in what ways these connections improve certain organizational outcomes, such as grant allocation (Faulk, Willems, McGinnis Johnson et al 2016;Paarlberg, Hannibal & Johnson 2020), inter-organizational collaboration (Ihm & Shumate 2019), or in spreading board governance practices (Yoon 2022). Following the terminology by Knox, Savage and Harvey (2006), this study instead treats the network structure as an object of inquiry in itself rather than an independent variable explaining some other outcome, hence speaking to studies explaining how board interlocks are formed, rather than their effects (Willems, van Puyvelde, Jegers et al 2015;Yoon 2023).…”
mentioning
confidence: 99%